The Impact of Financial Behavior and FinTech Utilization on Student Retention at Universitas Terbuka Kendari - Anfas Anfas; Arifuddin Mas’ud; H. Hendrian; Julia Safitri (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
This study employs a quantitative approach to examine the effect of financial behavior (X1) and fintech utilization (X2) on student study retention (Y). The population of this research consists of students at Universitas Terbuka Kendari, with a total sample of 204 respondents. Data were analyzed using linear regression, both in partial and multiple models. The findings reveal that: (1) Financial behavior has a significant impact on student retention, indicating that students who manage their finances more responsibly are more likely to complete their studies. (2) Fintech utilization also significantly affects student retention, as the ease of financial transactions facilitated by fintech supports students in meeting their academic obligations. (3) Collectively, financial behavior and fintech utilization explain 49.9% of the variance in student retention, underscoring the critical role of financial aspects in sustaining academic continuity, particularly within the context of Universitas Terbuka Kendari, a higher education institution operating through a distance learning system.